Binge Drinking–Induced Subtle Myocardial Injury. (25th June 2013) - Waszkiewicz, Napoleon; Szulc, Agata; Zwierz, Krzysztof
Abstract : Background: Most of the clinical, histopathological, and biochemical studies consider the effect of chronic alcohol intoxication on myocardial injury. Much less attention has been paid to acute alcohol (binge drinking)–induced cardiotoxicity, even though alcohol binging is much more common than alcohol dependence. Methods: We briefly present some of the binge drinking–induced "holiday heart" effects. The literature was searched to find effects of alcohol on heart. Results: In binge drinking, the literature has demonstrated transient myocardial subtle changes in cardiac magnetic resonance, increased serological markers of myocardial injury and inflammation, abnormal cardiac rhythm, changes in other biochemical and ultrastructural indices of myocardial dysfunction, as well as changes in metabolism, blood pressure, heart rate, thrombosis/fibrinolysis processes, and coronary vasoconstriction. Conclusions: Although acute low alcohol exposure has widely proven positive effect on myocardial function, heavy acute drinking frequent events are related to adverse cardiovascular effects.